2019
DOI: 10.1097/ajp.0000000000000676
|View full text |Cite
|
Sign up to set email alerts
|

Pain Catastrophizing and Function In Individuals With Chronic Musculoskeletal Pain

Abstract: Objectives: Pain catastrophizing (PC) is the most consistent psychosocial factor predicting of adjustment to chronic pain and may contribute to the development and long-term maintenance of chronic pain. The aim of this review was systematically review and critically appraise the concurrent and longitudinal associations between PC and both pain intensity and disability in individuals with chronic musculoskeletal pain (CMP). Materials and Methods: An elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(104 citation statements)
references
References 153 publications
3
97
1
3
Order By: Relevance
“…Furthermore, AEQ‐CTS was not uniquely associated with LBP intensity or disability. This is in contrast to considerable evidence for a link between catastrophizing and chronic pain in non‐athletes (Martinez‐Calderon, Jensen, Morales‐Asencio, & Luque‐Suarez, ) and athletes (Ghazaie et al, ). However, it is of note that catastrophizing is conventionally assessed using the Pain Catastrophizing Scale (Sullivan, Bishop, & Pivik, ) which summarizes the subscales magnification, helplessness and rumination (Adachi et al, ).…”
Section: Discussioncontrasting
confidence: 74%
“…Furthermore, AEQ‐CTS was not uniquely associated with LBP intensity or disability. This is in contrast to considerable evidence for a link between catastrophizing and chronic pain in non‐athletes (Martinez‐Calderon, Jensen, Morales‐Asencio, & Luque‐Suarez, ) and athletes (Ghazaie et al, ). However, it is of note that catastrophizing is conventionally assessed using the Pain Catastrophizing Scale (Sullivan, Bishop, & Pivik, ) which summarizes the subscales magnification, helplessness and rumination (Adachi et al, ).…”
Section: Discussioncontrasting
confidence: 74%
“…Together, these results indicate complex interrelationships between pain and catastrophizing. A recent systematic review and meta-analysis concerning pain catastrophizing in chronic pain found weak associations with pain intensity and disability from both cross-sectional and longitudinal perspectives [23]. The meta-analyses indicated prominent heterogeneity.…”
Section: Introductionmentioning
confidence: 96%
“…These factors can be part of an individual’s day-to-day life (e.g., stress [ 12 ] or social support [ 13 ]) or emerge in response to pain (e.g., fear of pain [ 14 ] or pain acceptance [ 15 ]). Although much of the focus of research on psychological factors and chronic pain has focused on maladaptive responses—in particular catastrophizing [ 16 ]—positive psychological factors could also potentially play an important role in the adjustment to persistent pain [ 17 , 18 ]. Recently, some pain adaptation paradigms have emerged aiming to explain why some people respond better than others to the chronic pain experience [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%